Relationship between Emotional Intelligence and Religiosity with Dark Triad of Personality of Corruption Prisoners - Kaumbur, Eva Silia; Hardjanta, George (COUNS-EDU: The International Journal of Counseling and Education, 2017)
This study aims to determine the relationship between emotional intelligence and religiosity with dark triad of personality of corruption prisoners. The data were obtained from 62 prisoners of Corruption in Kedungpane Semarang Prison selected by quota sampling. The research instruments used are Schutte Emotional Intelligence Scale (SEIS), The New Indices of Religious Orientation Revised (NIROR), and Short Dark Triad (SD3) to measure emotional intelligence, religiosity, and dark triad of personality. The results showed:  (1)  a relationship between emotional intelligence and religiosity together with dark triad of personality of corruption prisoners, (2) a positive correlation between emotional intelligence and dark triad of personality of corruption prisoners, (3) a negative correlation between intrinsic religious orientation and psychopathy, (4) a positive  correlation between extrinsic religious orientation and dark triad of personality of corruption prisoners, and (5) a positive  correlation between quest religious orientation and dark triad of personality of corruption prisoners.